A non-rigid point matching method with local topology preservation for accurate bladder dose summation in high dose rate cervical brachytherapy. (20th January 2016) - Chen, Haibin; Zhong, Zichun; Liao, Yuliang; Pompoš, Arnold; Hrycushko, Brian; Albuquerque, Kevin; Zhen, Xin; Zhou, Linghong; Gu, Xuejun
Abstract: GEC-ESTRO guidelines for high dose rate cervical brachytherapy advocate the reporting of the D2cc (the minimum dose received by the maximally exposed 2cc volume) to organs at risk. Due to large interfractional organ motion, reporting of accurate cumulative D2cc over a multifractional course is a non-trivial task requiring deformable image registration and deformable dose summation. To efficiently and accurately describe the point-to-point correspondence of the bladder wall over all treatment fractions while preserving local topologies, we propose a novel graphic processing unit (GPU)-based non-rigid point matching algorithm. This is achieved by introducing local anatomic information into the iterative update of correspondence matrix computation in the 'thin plate splines-robust point matching' (TPS-RPM) scheme. The performance of the GPU-based TPS-RPM with local topology preservation algorithm (TPS-RPM-LTP) was evaluated using four numerically simulated synthetic bladders having known deformations, a custom-made porcine bladder phantom embedded with twenty one fiducial markers, and 29 fractional computed tomography (CT) images from seven cervical cancer patients. Results show that TPS-RPM-LTP achieved excellent geometric accuracy with landmark residual distance error (RDE) of 0.7  ±  0.3 mm for the numerical synthetic data with different scales of bladder deformation and structure complexity, and 3.7  ±  1.8 mm and 1.6  ±  0.8 mm for the porcine bladder phantom with large and small deformation, respectively. The RDE accuracy of the urethral orifice landmarks in patient bladders was 3.7  ±  2.1 mm. When compared to the original TPS-RPM, the TPS-RPM-LTP improved landmark matching by reducing landmark RDE by 50  ±  19%, 37  ±  11% and 28  ±  11% for the synthetic, porcine phantom and the patient bladders, respectively. This was achieved with a computational time of less than 15 s in all cases with GPU acceleration. The efficiency and accuracy shown with the TPS-RPM-LTP indicate that it is a practical and promising tool for bladder dose summation in adaptive cervical cancer brachytherapy.